COVID-19 pandemic and mental health of educators in higher education institution: a systematic literature review - Abdul Rahman, Rahayu; Mohd Isa, Noor Saatila; Zamri, Norhayati; Pitaloka, Endang; Suyoto, Yohanes Totok; Yunus, Mohd Hadli Shah Mohamad (International Journal of Public Health Science (IJPHS), 2023)
Emergency transformation of the education system due to the COVID-19 increased mental and emotional disorders risks of educators in higher education institutions. Thus, this study aims to examine how COVID-19 impacts the mental well-being of educators, and also explore the contributing factors to these issues. A systematic review was conducted, involving the identification of scientific articles related to mental health, lecturers, professors, and COVID-19. The research was performed on two reputable publication databases, SCOPUS and Web of Science. Following pre-established inclusion and exclusion criteria, this study utilized PRISMA to select and analyze the research articles. Through this process, a total of 59 articles have been identified from the electronic databases, out of which seven articles were selected for evaluation. The findings indicate that a significant number of educators encountered various mental health challenges in the midst of the pandemic, including burnout, anxiety, depression, and stress. Numerous factors, such as an imbalance between job demand and job resources, a lack of support, personal factors, and other emergency remote teaching-related factors, all contribute to the issues. This study offers valuable insights that can be utilized to develop optimal practices for educators to address and manage their mental health and well-being in the future.